2021
DOI: 10.1136/bmjsit-2020-000072
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the relationship between surgeon procedure volume and complications after total knee arthroplasty using a propensity-matched cohort study

Abstract: ObjectivesThis study aimed to identify a threshold in annual surgeon volume associated with increased risk of revision (for any cause) and deep infection requiring surgery following primary elective total knee arthroplasty (TKA).DesignA propensity score matched cohort study.SettingOntario, Canada.Participants169 713 persons who received a primary TKA between 2002 and 2016, with 3-year postoperative follow-up.Main outcome measuresRevision arthroplasty (for any cause), and the occurrence of deep surgical infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 26 publications
3
14
0
Order By: Relevance
“…However, we would argue that the true surgical volume is the most important factor when determining the risk of revision in TKA surgery, as demonstrated by our study. 1 The findings in our study are echoed in the analysis by Yu et al, which concluded that from a number of outcomes evaluated, only surgical volume was associated with an increased risk of TKA 30-day readmission. 2 While it is recognized that highly experienced orthopaedic surgeons may deliver excellent patient outcomes regardless of a minimum volume, evidence suggests that higher surgical volumes result in better patient outcomes.…”
supporting
confidence: 69%
See 3 more Smart Citations
“…However, we would argue that the true surgical volume is the most important factor when determining the risk of revision in TKA surgery, as demonstrated by our study. 1 The findings in our study are echoed in the analysis by Yu et al, which concluded that from a number of outcomes evaluated, only surgical volume was associated with an increased risk of TKA 30-day readmission. 2 While it is recognized that highly experienced orthopaedic surgeons may deliver excellent patient outcomes regardless of a minimum volume, evidence suggests that higher surgical volumes result in better patient outcomes.…”
supporting
confidence: 69%
“…However, we would argue that the true surgical volume is the most important factor when determining the risk of revision in TKA surgery, as demonstrated by our study. 1 The findings in our study are echoed in the analysis by Yu et al , which concluded that from a number of outcomes evaluated, only surgical volume was associated with an increased risk of TKA 30-day readmission. 2 …”
supporting
confidence: 69%
See 2 more Smart Citations
“…In the recent article by Okoro et al , data from nearly 170 000 TKR recipient in Ontario, Canada, were analysed using a state of the art restricted cubic spline (RCS) analysis. 5 The authors identified an inflection point for increased probability for early revision or infection at 70 annual cases, after which the risk of complications plateaued. However, risk reduction continued even beyond an annual caseload of 70, highlighting the value of treatment by high-volume surgeons.…”
mentioning
confidence: 99%